Divorce Sues Through E-Court Process In The Binjai Religious Court in North Sumatera During The Covid-19 Pandemic - Muhammad Ridho Nasution; Sukiati Sukiati; Ramadhan Syahmedi Siregar (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2022)
The purpose of this study is to find out how the implementation of divorce lawsuits through the e-court at the Binjai Religious Court, the difference between filing an ordinary lawsuit and filing through an e-court, and the effectiveness of implementing a divorce lawsuit through the e-court at the Binjai Religious Court. This research is an empirical legal research, with a case study approach and a statutory approach. The data sources are primary and secondary data, the data collection techniques are observation, interviews and documentation. The results of the research are: First, the implementation of a lawsuit in the Binjai Religious Court in terms of registration through the e-court itself is of two kinds, namely advocates/legal entities and independent users. Second, the difference between an ordinary lawsuit and the submission through e-court is an ordinary lawsuit, a divorce suit is filed by the husband or wife or their proxies to the Court whose jurisdiction includes the defendant. Third, the effectiveness of the implementation of divorce lawsuits through e-court through the Binjai Religious Court of North Sumatra can be seen from saving time and money in the case registration process, as well as well-archived documents, accessible from various locations and media as well as a faster data retrieval process.